Isolation and diagnosis of bacteria isolated from selected stations of drinking water desalination in the Tigris River in Diyala Governorate using the Filters membrane method (Journal of the College of Basic Education, 2024)
Was Isolated Diagnosis of bacteria from drinking water models mansuriyah – shat –village- the Qasiris and the village of Al –Hawish along the Tigris River . where water was collected from the River . the study period was six months , November to April . In this study the focus was on the most important pathological bacteria Harmful . which affects human health , Especially cases of severe Diarrhoea and transported through the water for human beings . Human beings are a means of transmission Enterobacter , it s’ this bacteria , Escherichia coli , Sp Pseudomonas , SP Klepsiella , Shigella , Enterobacteraerogenes , Clostridium Perifringens ,Vibrio Cholera and Aeromonas SP, the presence of these microscopic organisms proof of water pollution . some chemical and biological factore have also been studied like the chemical requirment of oxygen COD , and the biological requirmentb of oxygen BOD and total outstanding materials . as well as the study of biological factors of the environments under study . found through results and abiotic factors . specifications of water samples taken from all stations from temperature (32-12)C°and salinity (0.1-0.5)G/L , AND Ph (8.4-9.4)COD (21-13)ppm and BOD (18-6)ppm. The results of abiotic factors are encouraging for bacteria growth in the invironments under study the results show that the River Tigris water is contaminated or highly contaminated . they are in appropriate as asource of drinking water , without multiple processing